Exploring collaborative strategies used by school management teams to sustain parental involvement in Xhariep District schools - Thabo Walter Sesinyi; Ntombizandile Gcelu (Perspectives in Education, 2023)
The annual analysis of schools’ results shows that Xhariep District still has many underperforming schools at the primary level, requiring continuous intervention from the Free State Department of Basic Education. This article explored collaborative strategies used by School Management Teams to sustain parental involvement in Xhariep District primary schools. The article is based on one of the authors' Masters dissertations. It is a qualitative research project that is based on the collaboration theory. After conducting a convenience sampling, 15 participants, including SMTs, teachers, and parents, were interviewed to determine their perception of parental involvement. The research used the inductive thematic analysis method, resulting in the identification of categories and trends and the interpretation of findings. The results of this study suggest that many societal issues contribute greatly to negative educational outcomes in the district. Most learners continue to become less interested in going to school, thus dropping out at the primary school level. The study also found that the contribution of parents to education is essential to ensuring a child's academic success, well-regulated school attendance, and acceptable levels of behaviour in and out of school. Therefore, the article recommends that parents be empowered and developed to have the necessary attributes essential to their participation and educational partnerships with schools.